Trafficking in Persons for Ransom and the Need to Expand the Interpretation of Article 3 of the UN Trafficking Protocol - Brhane, Mogos O (Anti-Trafficking Review, 2015)
As the nature of trafficking in persons continues to manifest itself in myriad ways all over the world, interpretation of the UN Protocol to Prevent, Suppress and Punish Trafficking in Persons, Especially Women and Children (Trafficking Protocol), should be broadened to include newly emerging practices that are similar in nature to those it has already embraced under its definition. The Protocol appears to encompass other forms of trafficking which are unnamed or unforeseen by the definition provided under Article 3. It is time to expand its spectrum. Northeast Africa is plagued by a unique form of trafficking in persons—trafficking in persons for ransom. This involves a practice where people are smuggled, abducted, kidnapped and tortured to compel their relatives and families to pay ransom money. Victims are nationals of Eritrea, Ethiopia, Sudan and South Sudan. However, as Northeast Africa hosts particularly high numbers of Eritrean migrants and the largest Eritrean diaspora globally, Eritreans are very vulnerable to being targeted for trafficking for ransom. As trafficking for ransom is an emerging trend, legal ramifications have never been studied in full. Few reports try to address legal issues around the phenomenon, and those that do only give it a few paragraphs of attention. There is need for a closer look at this form of trafficking.